Effects of molecular structure on the dielectric relaxation of substituted cellulose derivatives. Issue 1 (22nd January 2023) - Sobchuk, Andriy O.; Lazarenko, Maxim M.; Yablochkova, Kateryna S.; Dinzhos, Roman V.; Fialko, Nataliia M.; Lazarenko, Mykhaylo V.; Andrusenko, Dmitriy A.; Gryn, Svitlana V.; Brytan, Andriy V.; Alekseev, Alexander M.
Abstract: The paper discusses the temperature dependencies of the complex dielectric permittivity obtained at different frequencies for the substituted cellulose derivatives with various concentrations of the hydroxypropoxy group. The substituted cellulose derivatives are shown to undergo a low-temperature dielectric relaxation. The input of the dielectric relaxation into dielectric permittivity decreases when the OH groups in cellulose molecules are substituted by the methoxy groups. In contrast, when OH groups in cellulose molecules are substituted by hydroxypropoxy groups, the dielectric relaxation region shifts to higher temperatures, and its intensity increases. The dielectric spectroscopy method is shown to be a reliable method to estimate the degree of the substitutions of the hydroxyl groups with hydroxypropoxy groups in the cellulose derivatives, used in the pharmaceutical industry as drug carriers and drug delivery rate regulators.